Information Technologies: Analysis of patented inventions between continents for the period 1980 to 2010 - Restrepo Betancur, Luis Fernando (2016)
The knowledge related to the progress in the technological development, expressed as the number of patents registered by residents and non-residents, is of vital interest on the part of researchers, technology centers and government institutions. With this, it is possible to establish strategies routed to the increase of technology management and the invention with a view to minimize the gaps between developing countries and those highly innovative. This investigation is an analysis of the number of patents registered by the different continents: Africa, Asia, Europe, Latin (Latin America and the Caribbean, North America), Oceania, for the decades of the 80, 90 and the first of 2000. On the basis of the information disclosed by the World Intellectual Property Organization WIPO in relation to information technologies such as: technology computing, digital communication, telecommunications and audiovisual media. Noting that the analysis was performed for residents and nonresidents.  Used multivariate analysis of variance MANOVA with contrast canonical orthogonal type, using the general linear model GLM, with transformation of data based on the family BOX-COX. Highly significant difference was found between the Asian continent, with regard to the other geographical areas evaluated, in the number of patents registered for the variables mentioned above (p<0.0001). The main conclusion is that there is a large gap between Asia, North America and Europe with regard to Africa, Oceania and Latin America, in the number of patented inventions in this area of knowledge.